Design of test frame for the bending of composite structures - Quek, Yuan Yi. (2011)
The purpose of this project is to design a test frame for carrying out three and four point bending test on composite pipe. The test frame has been designed with features of adjustable pipe supports to vary ‘L’, the length of pipe, and adjustable four point press head which enables the frame to carry out a wide range of studies in three and four point bending. The test specimen is a fiberglass pipe where at the midpoint, there are rectangular strain gauges mounted at several positions around the circumference and a linear variable displacement transducer device to measure the deflection at the bottom of pipe. The experiments show that that the structural stiffness ‘K’ of specimen increases as the length of pipe ‘L’ is shortened and the attribution of deflection due to bending component and shear component are considered in terms of spring mass analogy. Then by using classical theories from mechanics of material, the experimental results of three point bending test give the value of overall longitudinal elastic modulus of fiberglass pipe as 14.0GPa which is near to the value of 12.5GPa which is specified by the manufacturer. The value of is 0.25GPa which is obtained by adopting graphical methods use for analyzing sandwich composite structure. In comparing the strain patterns of different pipe length in three point bending tests, it is observed that the effect of cross deformation will eventually overwhelm the effect of bending deflection as length of pipe decreases. Then, given the values of strain around the midpoint of pipe, the Mohr’s Circle is plotted to determine the principle strains experienced in the fibers direction. At the bottom tip of pipe, the fibers experienced compressive longitudinal and shear strain at with the magnitude of shear strain being much higher than the longitudinal strain. While at the side of pipe, the fibers experienced tensile longitudinal and shear strain with comparable magnitude. Finally for the three point bending test, the experimental results of deflection and strain are compared with the results of finite element analysis.